SCHOOL MANAGEMENT BASED ON ISLAMIC LAW SD Tahfizh TES Method (Tilawah Evaluasi Sederhana) In Baleendah, Bandung - Kadir, Amalliah; Endaryono, Bakti Toni; Rostandi, Usep Dedi (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Indonesia is a transcultural country that has been influenced by Western hegemony, which has led to the emergence of liberalism. This means that every person is free to express their innovation and creativity to influence others to follow them. The implementation of character education through Quran memorization is a conducive solution to address the challenges of the 21st century. The TES method (Simple Recitation Evaluation) has the effect of increasing closeness to the Quran, fostering Islamic character, and cultivating inner peace. The purpose of this research is to develop a Sharia-based school management model with four steps. The method used in this research is a qualitative descriptive method with a case study approach, employing data triangulation. Data collection was conducted through surveys using observation, interviews with snowball sampling to obtain in-depth and comprehensive answers, and documentation. The research instruments involved all school stakeholders, both internal and external, with primary and secondary data sources. The results of this study indicate that (1) Sharia-compliant planning, from vision to evaluation and revision, accelerates the smooth implementation of school operations. (2) The implementation of learning using appropriate tahfizh methods, professional teacher mastery in the classroom, and establishing flexible and appropriate partnerships can make students excel and help brain therapists, especially children with special needs, become haafizh Qur'an and have stable psychological conditions. (3) Continuous supervision by the foundation, school principal, and parents makes the school develop quickly and have many students. (4) The development of a Sharia-based school that considers students' psychological well-being and abilities, employee happiness, appropriate teacher placement and classroom layout, excellent service, and sound financial management makes the school outstanding.